PRODUCT PLACEMENT IN MOBILE GAMES AND THAI STUDENTS ATTITUDE TOWARD THE BRAND RECALLING - Taghipour, Amirhossein; Ahadi, Navidreza; Sornsaruht, Puris; Deebhijarn, Samart; Poopichayapongse, Preeya; Saechao, Torn; Jalali, Ali (PEOPLE: International Journal of Social Sciences, 2017)
Advertising in mobile games have increased significantly in recent years and are likely to be expanded. Nevertheless, the literature suggests that advertisement placement in games are, from time to time, counterproductive, and is regularly recognized as disturbing and possibly causing evading actions. For the reason of likelihood of evading, it is vital to inspect if players have a tendency toward paying attention to advertised products, even if they don’t recall them. The researchers conducted an experiment which measures the high/lowness of advertised product price, and types of advertisement themes such as pop-up message, commercial, and in-game elements and how well those advertised brands are recalled. Results propose that high priced products can lead to higher recalling and pop up message can be more effective than commercial and in-game elements. Moreover, gamers who were expressing higher attraction toward in-game elements believed that if they were the marketing manager, they would choose the in-game element option as product placement advertising theme because of the frequency of exposure and inability to disable it.